Image processing and analysis of microscopy images of red blood cells. - Soh, Wei Ting. (2012)
The flickering phenomenon of red blood cell (RBC) was discovered back in the 18th century. Flicker is defined as the spontaneous rhythmical and random alterations through a healthy RBC’s volume on a scale of 1-100 nanometers. This phenomenon is related to RBC’s deformability and its membrane mechanics. Therefore, it is important to understand this phenomenon in order to study the pathological conditions of RBC.